Group acceptance sampling plan for lifetime data using generalized Pareto distribution - Muhammad Aslam; Munir Ahmad; Abdul Razzaqe Mughal (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2010)
In this paper, a group acceptance sampling plan (GASP) is introduced for the situations when lifetime of the items follows the generalized Pareto distribution. The design parameters such as minimum group size and acceptance number are determined when the consumer's risk and the test termination time are specified. The proposed sampling plan is compared with the existing sampling plan. It is concluded that the proposed sampling plan performs better than the existing plan in terms of minimum sample size required to reach the same decision.
Keywords: 330; Group sampling plan; generalized Pareto distribution; consumer's risk; producer's risk; operating characteristics